The trends in e-learning implementation in tertiary education: A review of blended learning in China and other countries - XianJun Dai; Nur Suhaidah Sukor; He Sun (Penerbit UMS, 2023)
Blended learning is a combination of online learning and face-to-face learning. It is an important trend in the development of tertiary education in China and foreign countries. In recent years, the discussion of blended learning gradually moves from theory to practice, and more and more college teachers begin to pay attention to blended teaching design and put it into practice. This study attempts to give an overview on the topic of blended learning in tertiary education, with a comparison of Chinese and global perspectives. By using “blended learning” and “higher education” as the theme word, and through the advanced search function in CNKI (Core of Peking University /CSSCI) and Scopus database, this paper retrieved 356 and 2293 relevant journals respectively from 2004 to 2023. Utilizing a comparative approach, this study compared the retrieved data from CNKI and Scopus, sorted out the research context in China and foreign countries, analyzed the current research hot-spots, research topics and research trends of blended teaching in tertiary education using a comparative approach, and provided references for the future research in this field. The result showed that the research hot-spots includes the effectiveness of blended learning, blended learning models, blended learning strategies, and influencing factors of blended learning adoption. Furthermore, the study demonstrated a shift in research focus, from initial discussions to investigations into its pedagogical implications.